Confines of democracy : essays on the philosophy of Richard J. Bernstein - Castillo, Ramón del; Faerna García-Bermejo, Ángel Manuel.; Hickman, Larry A., 1942-; Bernstein, Richard J. (Value Inquiry Book Series, 2015)
The topics addressed by Richard J. Bernstein in his extensive and illuminating work span the stream of contemporary thought in several directions: ethics, politics, epistemology, philosophy of history, and social theory. In reflecting on them Bernstein has played an intermediary role between the most recognizable product of American philosophical tradition, id est Pragmatism, and such central trends in European 20th century thought as Marxism, Psychoanalysis, Critical Theory, and Hermeneutics. In this volume a host of prominent scholars from the United States, Europe, and Latin America pays tribute to Bernstein's lifelong reflection on such present human problems as: the achievements and the dilemmas of modern societies, the legitimation crisis of democracy, the uses and abuses of public space, the role of scientific knowledge and technology in shaping the modern life, the ethical and political interplay between identity and community, and the preconditions and limits of understanding in multicultural contexts. The fifteen essays in this book, accompanied by separate replies by Bernstein, are organized in four sections: "Bernstein, Rorty and American Pragmatism," "Epistemology and Hermeneutics," "Good, Evil and Judgment," and "Democratic Vistas." As Prof. Bernstein declares in his Preface, these "contributions are expressions of my own commitment to engaged fallibilistic pluralism."